Meta‐analysis of randomized controlled trials on atrial fibrillation ablation in patients with heart failure with reduced ejection fraction. Issue 11 (19th November 2018) - Smer, Aiman; Salih, Mohsin; Darrat, Yousef H.; Saadi, Abdulghani; Guddeti, Raviteja; Mahfood Haddad, Toufik; Kabach, Amjad; Ayan, Mohamed; Saurav, Alok; Abuissa, Hussam; Elayi, Claude S.
Abstract : Background: The role of catheter ablation (CA) is increasingly recognized as a reasonable therapeutic option in patients with atrial fibrillation (AF) and heart failure (HF). Hypothesis: We aimed to compare CA to medical therapy in AF patients with HF with reduced ejection fraction (HFrEF). Methods: We searched the literature for randomized clinical trials comparing CA to medical therapy in this population. Results: Six trials with a total of 775 patients were included. AF was persistent in 95% of patients with a mean duration of 18.5 ± 23 months prior enrollment. The mean age was 62.2 ± 7.8 years, mostly males (83%) with mean left ventricular ejection fraction (LVEF) of 31.2 ± 6.7%. Compared to medical therapy, CA has significantly improved LVEF by 5.9% (Mean difference [MD] 5.93, confidence interval [CI] 3.59‐8.27, P < 0.00001, I 2 = 87%), quality of life, (MD −9.01, CI −15.56, −2.45, P = 0.007, I 2 = 47%), and functional capacity (MD 25.82, CI 5.46‐46.18, P = 0.01, I 2 = 90%). CA has less HF hospital readmissions (odds ratio [OR] 0.5, CI 0.32‐0.78, P = 0.002, I 2 = 0%) and death from any cause (OR 0.46, CI 0.29‐0.73, P = 0.0009, I 2 = 0%). Freedom from AF during follow‐up was higher in patients who had CA (OR 24.2, CI 6.94‐84.41, P < 0.00001, I 2 = 81%. Conclusion: CA was superior to medical therapy in patients with AF and HFrEF in terms of symptoms, hemodynamic response, and clinical outcomes by reducing AF burden. However, these findings are applicable to the very specific patients enrolled in these trials.